Prevalence and characteristics of the Solitary Rectal Ulcer Syndrome among a Cohort of Iraqi Patients with Lower Gastrointestinal Bleeding. - Muntadher Abdullah; Nawal Al Khalidi; Kamal Lafta (مجله كليه طب الكندي)
Background: Solitary rectal ulcer syndrome (SRUS) is a benign, uncommon rectal disorder characterized by combination of symptoms, clinical findings, and histological abnormalities. It has wide range of presentations and variable endoscopic findings.